(3cJGH aj GdWH GdTQjas
(3ChdgG (B:s
(3GdMeO hGdTcQ dNGdb GdTaG heGfM GdUMI hHYO adeG cGfJ GdMceI CTQa GdYdhe GdEdgjI hCYXe GdehGgH GdQHGfjI CeQJ HhVY cJGH GdLfGH Whdhf HfG ai eYQaI eG jdRe cd ef EOYi gPg GdUfGYI s
(3BNQgG (B:s
(3hYdGL GdLQGMGJ jchf HVe TaJi GdLQM HGdQaGjO hPQ GdOhGA GdjGHS Ydjg hTOg Ef cGf UZjQkG hNha GdeQjV ef GdJedi aEf cGf GdLQM cHjQkG s
(3Ydjg Jedc dYHO Gddg SeMGJ SfI (B1239 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3GdWHs